2015
DOI: 10.1111/hpb.12326
|View full text |Cite
|
Sign up to set email alerts
|

Role of hepatic intra-arterial therapies in metastatic neuroendocrine tumours (NET): guidelines from the NET-Liver-Metastases Consensus Conference

Abstract: ObjectivesLiver metastasis from a neuroendocrine tumour (NET) represents a significant clinical entity. A multidisciplinary group of experts was convened to develop state-of-the-art recommendations for its management.MethodsPeer-reviewed published reports on intra-arterial therapies for NET hepatic metastases were reviewed and the findings presented to a jury of peers. The therapies reviewed included transarterial embolization (TAE), transarterial chemoembolization (TACE) and radioembolization (RE). Two system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
1
19

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(118 citation statements)
references
References 35 publications
1
97
1
19
Order By: Relevance
“…These patients are rarely cured surgically and thus are candidates for various forms of liver-directed therapies, particularly when the primary tumor is resected[1, 20, 21, •22, 68, •69, 70]. Liver-directed therapies include trans-arterial embolization (TAE), trans-arterial chemo-embolization(TACE), radioembolization or selective internal radiation therapy(SIRT), as well as radio-frequency ablation(RFA) and cytoreductive surgery.…”
Section: Summary Of Recent Advances/controversies In Management Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…These patients are rarely cured surgically and thus are candidates for various forms of liver-directed therapies, particularly when the primary tumor is resected[1, 20, 21, •22, 68, •69, 70]. Liver-directed therapies include trans-arterial embolization (TAE), trans-arterial chemo-embolization(TACE), radioembolization or selective internal radiation therapy(SIRT), as well as radio-frequency ablation(RFA) and cytoreductive surgery.…”
Section: Summary Of Recent Advances/controversies In Management Ofmentioning
confidence: 99%
“…Of these different ablative surgeries, RFA is the most frequently performed, often in combination with surgery, especially to remove isolated metastases in other hepatic locations[17, 20, 21, •22, ••24, •69, 7981]. Numerous criteria for when this should be considered have been proposed depending on the number of lesions, size, and proximity to vital structures[17, 20, 21, •22, ••24, •69, 7982]. Besides the use of RFA as an anti-tumor treatment, a number of studies have reported enhanced symptomatic control of functional NETs after its use[17, 20, 21, •22-, ••24, •69, 7983].…”
Section: Summary Of Recent Advances/controversies In Management Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…The few series with long-term follow-up reported 2-and 5-year survival ranging from 57% to 69% and from 45% to 55%, respectively. There appears to be little difference in the relative benefits of SIRT and other embolization techniques (117), but the quality and strength of the data do not allow firm conclusions (29). Nevertheless, SIRT may cause fewer side-effects and requires fewer treatments than chemoembolization techniques.…”
Section: Netsmentioning
confidence: 99%
“…If the metastatic tumor burden is predominantly located in the liver or even limited to it, radiological local-ablative procedures such as transarterial chemoembolization or bland transarterial embolization can be applied. 13 In addition, selective internal radiation therapy using 90 Y microspheres can be performed in NET patients with liverdominant disease manifestations, leading to a median overall survival (OS) of 70 months in these patients. 14 Gastroenteropancreatic NET with metastasis to the liver offers a typical scenario requiring a multimodal therapeutic setting, including surgery, chemotherapy, local treatment, and PRRT.…”
Section: Comprehensive Team Approachmentioning
confidence: 99%